Combining polysaccharide biosynthesis and transport in a single enzyme: dual-function cell wall glycan synthases - Davis, Jonathan K. (Frontiers in Plant Science, 2012)
Extracellular polysaccharides are synthesized by a wide variety of species, from unicellular bacteria and Archaea to the largest multicellular plants and animals in the biosphere. In every case, the biosynthesis of these polymers requires transport across a membrane, from the cytosol to either the lumen of secretory pathway organelles or directly into the extracellular space. Although some polysaccharide biosynthetic substrates are moved across the membrane to sites of polysaccharide synthesis by separate transporter proteins before being incorporated into polymers by glycosyltransferase proteins, many polysaccharide biosynthetic enzymes appear to have both transporter and transferase activities. In these cases, the biosynthetic enzymes utilize substrate on one side of the membrane and deposit the polymer product on the other side. This review discusses structural characteristics of plant cell wall glycan synthases that couple synthesis with transport, drawing on what is known about such dual-function enzymes in other species.